Kajian Literatur Potensi Penerapan Teknologi Plasma pada Kain Tekstil mengandung Bahan Alam sebagai Peningkat Antimikroba - Dara Azalea Wahdah; Gita Cahya Eka Darma; Fitrianti Darusman (Bandung Conference Series: Pharmacy, 2023)
Abstract. The use of fabric is one of the obligations of every human being used for clothing. Among them are the use of underware such as undershirts and head coverings such as hijab cuffs. In the conditions of using these fabrics, humid conditions are often formed which facilitate microbial growth. There is a technology in the form of plasma that can make textile fabrics have increased antimicrobial properties from natural materials soaked in these textile fabrics. The materials are patchouli oil and lemon oil which were tested against Staphylococcus epidermidis bacteria. This study aims to determine the effect of the application of plasma technology on the antimicrobial properties of textile fabrics. The results obtained from the journals that have been analyzed, it is found that plasma technology can affect textile fabrics as evidenced by a reduction in weight, an increase in absorbency that can create a deposit of active substances so that the antimicrobial activity of active substances increases. The inhibition diameter obtained for lemon oil was 11.75 increasing to 13.53 and for patchouli oil was 11.25 to 13.05 mm. Keywords: Plasma technology, undershirt, hijab cuff, lemon oil, patchouli oil. Abstrak. Penggunaan kain menjadi salah satu kewajiban setiap manusia yang digunakan untuk pakaian. Diantaranya penggunaan underware seperti kaos dalam dan penutup kepala seperti manset hijab. Pada kondisi penggunaan kain tersebut sering terbentuk kondisi lembab yang memudahkan pertumbuhan mikroba. Terdapat teknologi berupa plasma yang dapat membuat kain tekstil memiliki sifat antimikroba yang meningkat dari bahan alam yang direndam pada kain tekstil tersebut. Bahan tersebut berupa minyak nilam dan minyak lemon yang diujikan terhadap bakteri Staphylococcus epidermidis. Penelitian ini bertujuan untuk mengetahui pengaruh penerapan teknologi plasma terhadap sifat antimikroba pada kain tekstil. Hasil penelitian yang diperoleh dari jurnal yang telah di analisis, didapatkan bahwa teknologi plasma dapat memengaruhi kain tekstil dengan dibuktikan adanya pengurangan bobot, peningkatan daya serap yang dapat membuat tempat deposit zat aktif sehingga aktivitas antimikroba zat aktif meningkat. Diameter hambat yang diperoleh untuk minyak lemon sebesar 11,75 meningkat menjadi 13,53 dan untuk minyak nilam sebesar 11,25 menjadi 13,05 mm. Kata Kunci: Teknologi plasma, kaos dalam, manset hijab, minyak lemon, minyak nilam.